Dicamptus Szépligeti (Hymenoptera: Ichneumonidae: Ophioninae) from Vietnam - Pham, Nhi Thi; Matsumoto, Rikio; Shimizu, So (Zootaxa, 2020)
A new species of Darwin wasp of the genus Dicamptus Szépligeti (Hymenoptera: Ichneumonidae: Ophioninae), D. curvus Pham, Matsumoto & Shimizu sp. nov., is described on the basis of type specimen from Lai Chau Province, northwest Vietnam. The new species probably belongs to the giganteus species group and is easily distinguishable from the other species of the group by the smaller indices of fore wing AI and CI as well as the form of sclerites. Two species, D. cantoni Gauld & Mitchell and D. reticulatus (Cameron), are recorded for the first time from Vietnam; and additional distribution records for D. nigropictus (Matsumura) in Vietnam are provided. Through the present study, a total of four Dicamptus species have been recognized in Vietnam and illustrated.